Complex Number Problem #2

Show that e^{i \theta} + e^{-i \theta} = 2 cos \theta. Hence show that \mathrm{cos}^3 \theta = \frac{1}{4} (\mathrm{cos}3 \theta + 3 \mathrm{cos} \theta)

For the first part, we can simply apply Euler’s Formula, that is e^{i \theta} = \mathrm{cos} \theta + i \mathrm{sin} \theta

e^{i \theta} + e^{-i \theta}
= \mathrm{cos} \theta + i \mathrm{sin} \theta + \mathrm{cos} (- \theta) + i \mathrm{sin} (- \theta)
= \mathrm{cos} \theta + i \mathrm{sin} \theta + \mathrm{cos} \theta - i \mathrm{sin} \theta
= 2 \mathrm{cos} \theta

The next part is a little more tricky, and since its hence, we will use what we solved previously to help us.

e^{i \theta} + e^{-i \theta} = 2 cos \theta
\Rightarrow cos \theta = \frac{1}{2}(e^{i \theta} + e^{-i \theta})

\mathrm{cos}^3 \theta

= (\mathrm{cos})^3

= [\frac{1}{2}(e^{i \theta} + e^{-i \theta})]^3

= \frac{1}{8}(e^{i \theta} + e^{-i \theta})^3

= \frac{1}{8}(e^{i 3\theta} + 3 e^{i 2\theta}e^{-i \theta} + 3 e^{i \theta}e^{-i 2\theta} + e^{-i 3\theta})

= \frac{1}{8}(e^{i 3\theta} + 3 e^{i \theta} + 3 e^{-i \theta} + e^{-i 3\theta})

= \frac{1}{8}\{\mathrm{cos} 3\theta + i \mathrm{sin} 3\theta + 3(\mathrm{cos} \theta + i \mathrm{sin} \theta) + 3[\mathrm{cos} (-\theta) + i \mathrm{sin} (-\theta)] + \mathrm{cos} (-3\theta) + i \mathrm{sin} (-3\theta) \}

= \frac{1}{8}(\mathrm{cos} 3\theta + i \mathrm{sin} 3\theta + 3\mathrm{cos} \theta + 3i \mathrm{sin} \theta + 3\mathrm{cos} \theta - 3i \mathrm{sin} \theta + \mathrm{cos} 3\theta - i \mathrm{sin} 3\theta)

= \frac{1}{8}(\mathrm{cos} 3\theta + i \mathrm{sin} 3\theta + 3\mathrm{cos} \theta + 3i \mathrm{sin} \theta + 3\mathrm{cos} \theta - 3i \mathrm{sin} \theta + \mathrm{cos} 3\theta - i \mathrm{sin} 3\theta)

= \frac{1}{8}(\mathrm{cos} 3\theta + 3\mathrm{cos} \theta + 3\mathrm{cos} \theta + \mathrm{cos} 3\theta)

= \frac{1}{8}(2\mathrm{cos} 3\theta + 6\mathrm{cos} \theta )

= \frac{1}{4}(\mathrm{cos} 3\theta + 3\mathrm{cos} \theta )

Just for fun…

2e^{\frac{5\pi}{6}i} + \frac{1}{2e^{\frac{5\pi}{6}i}}
= 2e^{\frac{5\pi}{6}i} + \frac{1}{2}2e^{\frac{-5\pi}{6}i}
= 2 [\mathrm{cos}(\frac{5\pi}{6}) + i \mathrm{sin}(\frac{5\pi}{6})] + \frac{1}{2 } [\mathrm{cos}(\frac{-5\pi}{6}) + i \mathrm{sin}(\frac{-5\pi}{6})]
= 2 (\frac{-\sqrt{3}}{2} + i \frac{1}{2}) + \frac{1}{2} (\frac{-\sqrt{3}}{2} - i \frac{1}{2})
= -\sqrt{3} + i + \frac{-\sqrt{3}}{4} - i\frac{1}{4}
= -\frac{5\sqrt{3}}{4} + \frac{3}{4}i

e^{x+yi} = (1+i)^6 = [\sqrt{2}e^{i\frac{\pi}{4}}]^6
e^{x+yi} = 8e^{i\frac{3\pi}{2}}
e^x \times e^{yi} = 8 e^{i\frac{3\pi}{2}}
\Rightarrow e^x = 8 \Rightarrow x = \mathrm{ln}8 = 3 \mathrm{ln}2
\Rightarrow y = \frac{3\pi}{2} - 2\pi = \frac{-\pi}{2}

Complex Number Problem #1

Comments
    pingbacks / trackbacks

    Leave a Comment

    5 × 3 =

    Contact Us

    CONTACT US We would love to hear from you. Contact us, or simply hit our personal page for more contact information

    Not readable? Change text. captcha txt

    Start typing and press Enter to search